Efficient method for propargylation of aldehydes promoted by allenylboron compounds under microwave irradiation - Freitas, Jucleiton J. R.; Freitas, Queila P. S. B.; Andrade, Silvia R. C. P.; Freitas, Juliano C. R.; Oliveira, Roberta A.; Menezes, Paulo H. (Beilstein Journal of Organic Chemistry, 2020)
The propargylation of aldehydes promoted by microwave irradiation using allenylboron compounds in a chemo- and regioselective way is described. The corresponding products were obtained in short reaction time, high yield and purity without the need of any solvent when allenylboronic acid pinacol ester was used, or using a minimal amount of acetone when potassium allenyltrifluoroborate was used.
Keywords: boron compounds; microwave; propargylation; regioselectivity; synthesis